Pectinariidae (Annelida, Polychaeta) from the coastal waters of China, with description of new species and new records - Zhang, Jinghuai; Hutchings, Pat; Qiu, Jian-Wen (Zootaxa, 2022)
Pectinariidae Quatrefages, 1865 is widely distributed, and easily distinguished from other polychaetes by their characteristic semi-circular operculum with two rows of stout golden paleae and “ice-cream cone”-shaped tubes made of sand or shell fragments. A total of 387 specimens of pectinariids from the coastal waters of China were examined. Eleven species belonging to three genera of pectinariids were identified and described, including four new species (Amphictene jianqingi n. sp., Pectinaria lizhei n. sp., Pectinaria dayaensis n. sp., Pectinaria xiukaii n. sp.) and one new record (Pectinaria plurihamus Choi, Jung & Yoon, 2017). A key to genera of Pectinariidae and recorded species from Chinese waters is given. Based on partial sequences of five genes (COI, 16S rDNA, 18S rDNA, 28S rDNA and H3), the phylogenetic relationship of pectinariids is analyzed. The three new species Amphictene jianqingi n. sp., Pectinaria lizhei n. sp. and Pectinaria dayaensis n. sp. with molecular data are well supported. Three species of Lagis (L. koreni, L. bocki and L. plurihamus), five species of Pectinaria (P. dayaensis, P. dodeka, P. gouldii, P. lizhei and P. torquata), and three species of Amphictene (A. auricoma, A. alata and A. jianqingi) do not form a well supported clade, which requires more detailed analyses.